Cancioneiro folclórico infantil e estigma: uma análise a partir da educação em direitos humanos - Niceias, Mayara Divina Teles (2016)
This is an interdisciplinary research aiming to comprehend the stigma on the folkloric children’s songbook from human rights. The main objective is to analyze how the stigma can be negatively reinforced at childhood and within scholar context from execution of folkloric songs in this environment. The stigma is addressed here as one of the possibilities of its manifestation through the folkloric children’s songbook in child education, once it is known that the stigma can occur through various other forms. The need to investigate this matter emerged from my experience as a musical educator in the classroom. These experiences made me realize that the songs we sing with children exert significant influence in their relationship with others. When these songs’ content present words, terms or representations linked to the stigma, preconception and discrimination behavior may be reinforced. It is easier today to find children aged between two and five years old who know at least one song from Brazilian’s folklore. Therefore, a cutout to analyze children included in this age group in child education was made. The methodology of this study was the analysis of content from books based on the folkloric children’s songbook, developed to be applied in the scholar context. The selected songs allowed establishing the following stigma categories: gender, old age, ugliness, corporal, learning difficulty, and professional. According to the analysis of the songs’ content, it was possible to conclude that the folkloric children’s songbook, when applied in the classroom without any concern regarding lyrics, can be a reinforcement tool towards stigma. On the other hand, discussing these contents from particular experiences of each student may promote a dialogue capable of making the subjects involved open to the difference in a purpose of education for diversity and preparation of a more just and egalitarian society in their differences.